2001
DOI: 10.4049/jimmunol.166.3.2080
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Estrogen Therapy Ameliorates Experimental Autoimmune Encephalomyelitis in Two Different Inbred Mouse Strains

Abstract: It has been proposed that homeostatic levels of estrogen can enhance female susceptibility to autoimmunity, whereas the heightened levels of estrogen associated with pregnancy are protective. This hypothesis was tested using the mouse model of experimental autoimmune encephalomyelitis (EAE). Diestrus (<100 pg/ml in serum) levels of 17β-estradiol were found to significantly reduce the clinical manifestations of active EAE in both male and female mice. Estriol was also effective but at doses below those p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
289
3
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(315 citation statements)
references
References 56 publications
(51 reference statements)
20
289
3
3
Order By: Relevance
“…27 The protective effect of E2 was associated with diminished migration of encephalitogenic T cells into the CNS and effects on dendritic cells and macrophages. 28,29 Recently, we also showed using knockout mice that Esr1 is required for the protective effect of E2 on EAE.…”
Section: Discussionmentioning
confidence: 99%
“…27 The protective effect of E2 was associated with diminished migration of encephalitogenic T cells into the CNS and effects on dendritic cells and macrophages. 28,29 Recently, we also showed using knockout mice that Esr1 is required for the protective effect of E2 on EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological or pharmacological fluctuations in estrogen levels have been recognised since a long time to play a regulatory role in EAE ( [13,108,111,119,150]). Oral administration of low doses of estrogenic hormones, 17beta-estradiol and ethinyl estradiol, drastically reduce the severity of EAE and this effect was reconciled with a decrease in the production of inflammatory Th1 cytokines (such as inteferon-c (IFN-c), Tumor Necrosis Factor-a (TNF-a), Interleukin (IL)-1 and IL-6), chemokines/receptors, while increasing the expression of anti-inflammatory Th2 cytokines (including IL-4, IL-5 and Transforming Growth factor-b3 (TGF-b3)) ( [13,108,150,222]).…”
Section: Estrogens and Multiple Sclerosismentioning
confidence: 99%
“…Oral administration of low doses of estrogenic hormones, 17beta-estradiol and ethinyl estradiol, drastically reduce the severity of EAE and this effect was reconciled with a decrease in the production of inflammatory Th1 cytokines (such as inteferon-c (IFN-c), Tumor Necrosis Factor-a (TNF-a), Interleukin (IL)-1 and IL-6), chemokines/receptors, while increasing the expression of anti-inflammatory Th2 cytokines (including IL-4, IL-5 and Transforming Growth factor-b3 (TGF-b3)) ( [13,108,150,222]). This observation together with the fact that no infiltrating lymphocytes were found in the hormone-treated animals, led to the conclusion that estrogens protects mice from EAE by inhibiting the recruitment of T cells and macrophages into the CNS.…”
Section: Estrogens and Multiple Sclerosismentioning
confidence: 99%
“…After puberty, MS occurs two times more frequently in the female than the male (Czlonkowska et al, 2005;Hughes, 2004), but pregnancy has a protective effect (Confavreux et al, 1998). Treatment of MS in humans and experimental allergic encephalomyelitis (EAE) in mice by estrogens ameliorates these diseases (Bebo et al, 2001;Morales et al, 2006;Soldan et al, 2003). An immunomodulatory effect had been suspected (Lang, 2004), but it has recently been shown that in EAE, estradiol exerts its ameliorating effect via ERa receptors in CNS-resident cells, not in lymphocytes (Garidou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%